PENGARUH LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PADA PT BPR PRISMA DANA MANADO - WAROUW, CHRISTIAN; Sumayku, Sontje M.; Tumbel, Tinneke M. (JURNAL ADMINISTRASI BISNIS, 2017)
The success of an institution or organization is determined by the quality of the components and systems in which the components are interconnected, one of which is human resources. To achieve the goals of an organization then what managers need to do is to encourage employees to work according to what the organization wants. One of them through the provision of motivation to employees, because with the high work motivation in a person, it will arise employee morale in the employee who will create a good work productivity. How working environment conditions against employee motivation anda how the effects of work environment on employee motivation motivation PT BPR. Prisma Dana. This research includes quantitative research because the formulation of hypotheses and variabels used is taken from existing theory, tha is work environment theory for insependent variable and work motivation theory for the dependent variable. Research time is estimated approximately 1 month, to obatin the data needed in this study, researchers conductedresearch on PT. BPR Prisma Dana Manado. As for the population in this study are employees of PT. BPR Prisma Dana Manado totaling 60 peoples. And i took the sample to be studied amounted to about 30 people. Analysis of the data above shows that the work environment has a significant positive influence on the motivation of work PT. BPR Prisma Dana Manado. This is indicated by several tests conducted on work environment variabels. Like t test above. In simple correlation analysis shows that there is a close relationship between work environment with work motivation. The results of these studies prove an simultaneously answer the hypothesis that there is influence between the work environment on employee motivation in PT. BPR Prisma Dana Manado. There is a significant influence between work environment on employee work motivation PT. BPR Prisma Dana Manado. By looking at the average achievement of all working environment indicators achieved, presumably for all employees of PT. BPR Prisma Dana Manado still maintains the achievements that have been obtained. Keywords : Work Environment, Work Motivation